Вплив радянської влади на формування студентського складу Волинської духовної семінарії - Федчук, Олександр; Fedchuk, Oleksandr (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті розглянуто контроль радянської влади над складом студентів Волинської духовної семінарії протягом її існування в 1945–1964 рр. При цьому наведено характерні приклади ставлення влади до семінаристів та проаналізовано причини, що спонукали до усунення з навчального закладу окремих із них. Розкрито методи, якими уповноважений Ради в справах Руської православної церкви добивався відрахування із семінарії небажаних осіб. The article is devoted to the control of the Soviet government of the part of students of the Volyn theological Seminary during its existence in 1945–1964 years. One was given the following typical examples of attitude of power to all seminarians and analyzed the reasons of the exclusion some of them from the educational institution. In particular, it was shown the attitude of the regime towards the representatives of different social groups who have revealed a desire to study in the Seminary, and to persons suspected of disloyalty to the Soviet reality. It was clarified the methods by which the Commissioner of the Council for Russian Orthodox Church attained exclusion of undesirable persons from the Seminary, and also was paid attention to the attitudes to the representatives of the Seminary at different periods of its existence.
The Impact of Soviet Power on the Formation of the Volyn Theological Seminary Students
Keywords: Волинська духовна семінарія; уповноважений; націоналістичний рух; Михайло Діденко; Сильвестр Богданов; Анатолій Федулов; Volyn theological Seminary; the Commissioner; the nationalist movement; Mikhail Didenko; Sylvester Bogdanov; Anatoly Fedulov